Intra-articular versus intravenous tranexamic acid in total hip arthroplasty: A systematic review and meta-analysis of randomized controlled trials - Jaroslaw Pecold; Michal Pruc; Gabriella Nucera; Krzysztof Kurek; Lukasz Szarpak; Mahdi Al-Jeabory (Advances in Medicine, Psychology, and Public Health)
Introduction: Given the increasing prevalence of hip dysfunction and the consequent rise in total hip arthroplasty procedures, our research aims to elucidate the optimal administration route of tranexamic acid to minimize perioperative complications and enhance patient. Methods: The BioMedCentral, PubMed, EMBASE, Scopus, and Cochrane Central Register databases were searched for pertinent studies published up until January 12, 2024. Randomized and quasi-randomized clinical trials comparing intravenous versus intra-articular tranexamic acid in adult patients under total hip arthroplasty were included. Pooled analysis was conducted using Review Manager v. 5.4 software (RevMan). The level of statistical significance was set at p < 0.05. Results: Nineteen trials were included in the meta-analysis. Hemoglobin drops after IV-TXA compared to IA-TXA showed no statistically significant differences (SMD = -0.08; 95%CI: -0.41 to 0.24; p=0.61). The situation was similar for hemoglobin drop (SMD = 0.03; 95%CI: -0.10 to 0.17; p=0.62). Total blood loss for IV-TXA was 935 ± 527 mL, compared to 962 ± 519 mL for IA-TXA (SMD = -0.07; 95%CI: -0.19 to 0.05; p=0.23; Figure 6). The need for blood transfusion was noted in 8.1% of IV-TXA-treated patients and 8.3% of IA-TXA-treated patients (OR = 0.95; 95%CI: 0.66 to 1.38; p=0.79). Discussion and Conclusions: Both the intravenous and intra-articular tranexamic acid administration showed the same level of effectiveness in limiting blood loss, lowering post-operative complications, and minimizing overall adverse events in total hip arthroplasty. These approaches may be used interchangeably at the clinician's discretion without determining the superiority of any method. Moreover, it is vital to include tranexamic acid in the guidelines since it should be frequently used in any operation of this kind.